Knowledge and Sacredness - Rousseau, Jérôme (Culture, 1987)
The importance of the notion of sacredness is well recognized, but its central characteristics remain elusive. A solution can be found by shifting the focus of attention from the objects, persons or rituals which are deemed to be sacred to the statements about those objects. Such statements are accepted by the believer as unquestionably true while being unprovable. Sacredness is thus a feature of statements, not of objects. Sacredness is a procedure whereby a statement may be deemed to be true in the absence of the usual modes of verification, and it thus defines a particular kind of knowledge, distinct from common sense.